Method for Predicting the Liquid-Sloshing Characteristics of a Microsatellite Propulsion System - L. Teng; T. Meng; Zh. H. Jin (International Journal of Aerospace Engineering)
In this study, a method for establishing a prediction model for the liquid-sloshing characteristics of microsatellite propulsion systems is proposed. The ideal states of the liquid-sloshing characteristics are considered for the following three models: (1) storage tank, (2) coupled storage tank and microsatellite, and (3) coupled storage tank and microsatellite with a deployment mechanism. The smoothed-particle hydrodynamics method is implemented in ABAQUS to study the effect of sloshing on a storage tank and microsatellite disturbance for the above three cases. Relationship models between the sloshing time, sloshing angular velocity, amount of fluid filled, and satellite attitude angular velocity are established. The analysis results show that the disturbance angular velocity of the empty storage tank and sloshing angular velocity have a linear relationship. Furthermore, the disturbance angular velocity of the liquid-filled storage tank exhibits a surface relationship with the sloshing angular velocity and amount of fluid filled in a three-dimensional coordinate system. Additionally, the disturbance angular velocity in the liquid-filled state of the storage tank is higher than that of the empty storage tank, and the degree of disturbance decreases with the increase in the mass of the coupling. The disturbance of the storage tank and microsatellite with the deployment mechanism is 10−2°/s when the angular velocities of the satellite are ωx′=3, ωy′=3, and ωz′=2. The maximum and minimum deviations between the calculation and simulation results of the three models are 7.6% and 1.1%, respectively. The model is used to predict the disturbance angular velocity of the microsatellite. When the calculation results of the model are compared with the orbit satellite data, the maximum and minimum disturbance angular velocity deviations occur in the y and z directions with a deviation of 43.36% and 14.86%, respectively. This demonstrates the accuracy of the analysis and model. The results of this study can provide theoretical guidance for the engineering design and attitude and orbital control of a microsatellite propulsion system.